TUGAS DAN TANGGUNGJAWAB GURU DALAM EVALUASI PEMBELAJARAN AQIDAH AHKLAK DI MAN 1 KOTA BIMA - Aida, Aida; Idhar, Idhar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2023)
Evaluation is an activity carried out by every teacher, as an educator there must be an assessment activity (evaluation) of students because with this activity, teachers will assess the extent of potential their students have, students' characters are diverse therefore teachers must be patient and do things that are positive for his students. As a teacher, especially a teacher of moral aqidah, it is not only the evaluation of the material that is seen and assessed. However, teachers must assess the morals of each student, both in their words and actions. Because being a teacher of moral aqidah gives positive rights to their students to move towards the best path of Allah SWT. Therefore, the evaluation carried out by the moral aqidah teacher is not only about the material but also assessing their morals, because it is their morals that lead them to the pleasure of Allah SWT.